Hábitat rural productivo. Eco – hábitat modelo de ocupación productiva en zonas rurales (2022)
The project reasonably seeks the approach of a model of productive occupation in rural areas of Colombia, starting from understanding what the rural area is and what role it plays for the population. Through the interpretation and design of a UAF (Family Agricultural Unit) the distribution of clearly productive spaces is proposed for the potentialization of economic resources of the population and the new interaction with contemporaneity, supported in a sustainable way, allowing the support of the natural resources without overloading or exploiting them.